Analysis of Misconceptions on Material Solubility and Solubility Product (Ksp) Using a Four Tier Diagnostic Test Instrument - Priyasmika, Rendy (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2023)
Solubility and solubility product (Ksp) have the potential to be chemical materials that can cause misconceptions in students. The characteristics of material that are abstract, concrete and contain mathematical calculations are often the reason this material is considered difficult to understand. This research aims to analyze the misconceptions experienced by students regarding solubility and Ksp material. This research uses a descriptive method with a quantitative approach. The population of this study were all students of class XI Science at SMAN 1 Pronojiwo and all of them were the sample in this study. The sampling technique used is a saturated sample. The data collection instrument developed and used in this research is a four tier diagnostic test instrument. The data analysis technique uses quantitative descriptive which is guided by the results of the percentage of misconceptions experienced by students in each sub-concept of solubility and Ksp material as well as each question item. Based on the research results, it was identified that in general students' misconceptions regarding solubility and Ksp material were in the low category with a percentage of 23.35%. The highest percentage of misconceptions was identified in the sub-concept of the influence of pH on solubility at 26.62%. Meanwhile, the lowest percentage of misconceptions was identified in the sub-concept of determining the solubility(s) of salts or hydroxides that are difficult to dissolve at 17.48%.